The Impact of Price Perception, Location, and Facilities on Purchase Decisions (a Case Study of Al-Azfar Collection Boutique in Surabaya) - Widi harliana; Endah Budiarti , (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This thesis uses quantitative research to assess whether price, location, and facilities affect purchase decisions both individually and collectively at the Al-Azfar Boutique in Surabaya. The study employs a descriptive quantitative approach with a sample size of 99 respondents who frequently shop at the boutique. Sampling was carried out using probability sampling, and data was collected via a Likert-scale questionnaire. To validate and analyze the research, validity tests, reliability tests, classical assumption tests, multiple linear regression tests, t-tests, and F-tests were used. The results indicate that, simultaneously, price, location, and facilities significantly affect purchase decisions, as evidenced by a significance value of 0.000, which is less than 0.05. This means that price, location, and facilities collectively influence purchase decisions. Specifically, price significantly impacts purchase decisions, with a significance value of 0.000 (less than 0.05) and a t-value of 6.427 (greater than 1.98498). Conversely, location does not have a significant effect on purchase decisions, with a significance value of 0.224 (greater than 0.05) and a t-value of 1.223 (less than 1.98498). Facilities also do not significantly affect purchase decisions, with a significance value of 0.81 (greater than 0.05) and a t value of 1.765.